Marine Collagen Substrates for 2D and 3D Ovarian Cancer Cell Systems - Paradiso, Francesca; Fitzgerald, Joan; Yao, Seydou; Barry, Frank; Taraballi, Francesca; Gonzalez, Deyarina; Conlan, R. Steven; Francis, Lewis (Frontiers in Bioengineering and Biotechnology, 2019)
A fundamental structural component of extracellular matrix in all connective and interstitial tissue, collagen is the most abundant protein in the human body. To date, mammalian collagens sources represent the golden standard for multiple biomedical applications, while marine-derived collagens have largely been used in industry (food, pharmaceutical and cosmetic), with little use in research and clinical applications. Herein we demonstrate the effective use Rhizostoma Pulmo jellyfish collagen, a source of biocompatible, sustainable collagen for 2D and 3D cell culture, addressing the global drive for technological developments that result in the replacement of animals and their derived products in research. Jellyfish collagen harbours similar structural features of mammalian collagen type I, despite differing slightly in amino acid content. Jellyfish collagen supports ovarian cancer (OvCa) cell line proliferation, cellular morphology and expression of epithelial to mesenchymal transition markers, supporting the use of R. pulmo as a non-mammalian collagen cell culture substrate. Furthermore, R. pulmo collagen is effective in 3D device fabrication such as sponges where it mimics tissue architecture complexity. OvCa cells migrated and differentiated within the R. pulmo collagen 3D scaffolds confirming its suitability for advanced cell culturing applications, providing an excellent alternative to mammalian collagen sources for the culture of human cells.